Method for treating non-water-based drilling fluid by using organic modified ferric salt
By using organic modified iron salts to catalyze and coordinate the treatment of waste non-aqueous drilling fluid in thermal distillation, the problems of high energy consumption and low recovery in the prior art are solved, and efficient resource recovery and energy consumption reduction are achieved.
Patent Information
- Application Number
- CN202411530085.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-30
- Publication Date
- 2025-03-28
AI Technical Summary
In the prior art, when dealing with waste non-aqueous drilling fluid, the thermal distillation method consumes a high energy consumption, and the existing agents do not recover high waste oil-based drilling chips with high solid phase content, which makes it difficult to recover resources.
Organic modified iron salts are used to mix and stir with waste non-aqueous drilling fluid and then distilled. The catalytic synergistic thermal distillation is used for organic modified iron salts such as iron dodecyl sulfonate or iron dodecyl benzene sulfonate to destroy the stability of the multiphase colloid of the drilling fluid, and achieve oil-water separation and resource recovery.
It improves the efficiency of thermal distillation treatment and oil phase recovery rate, reduces energy consumption, and realizes the resource utilization and harmless disposal of waste non-water-based drilling fluid.
Smart Images

Figure CN119701415A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of petroleum and natural gas / the technical field of drilling fluid recycling and treatment, and specifically relates to a method for treating non-aqueous drilling fluid with organic modified iron salt. Background Art
[0002] Because non-aqueous drilling fluids have many advantages such as good lubricity, resistance to salt and calcium corrosion, high temperature resistance, good inhibition, good well wall stability, and reusability, they are widely used in special process wells, complex formations, and deep-water ocean oil drilling.
[0003] Waste non-aqueous drilling fluid is difficult to recycle due to the intrusion of inferior and harmful solid phases during drilling operations. Because it contains base oils such as diesel and white oil, it is classified as a national hazardous waste and has become a technical problem restricting the clean production of oil fields. At present, thermal distillation is one of the mainstream technologies for the reduction, harmlessness and resource utilization of waste non-aqueous drilling fluid. It has the advantages of being fast and efficient; but there is a problem of high energy consumption. Therefore, it is necessary to optimize the thermal distillation method to treat waste non-aqueous drilling fluid system to improve distillation efficiency and reduce energy consumption.
[0004] After multiple cycles of use, discarded non-aqueous drilling fluid (an oil-in-water type multiphase colloidal mixture composed of oil, water, organic solid particles such as asphaltene, inorganic solid particles such as drill cuttings, polymer compounds and other chemical substances) is water dispersed in oil in the form of small droplets, the water phase is the inner phase or dispersed phase, the oil is the outer phase or dispersed medium, and adsorbed at the interface to form an interfacial film, which ensures the stability of the emulsion. On the other hand, the adsorption and synergistic effect between heavy oil components or inorganic particles form a double-layer interfacial film, which hinders the aggregation of droplets. Therefore, there are problems such as high emulsification degree, high viscosity, and difficulty in resource recovery. However, the oil-in-water emulsion is an unstable system, and its stability is only relative and temporary. The stable structure of the drilling fluid interfacial film can be effectively reduced through chemical or particle demulsifiers, input of physical energy (such as heat, electromagnetic waves, microwaves, etc.) and biological effects, so as to achieve effective separation of the water-oil-solid three phases.
[0005] The Chinese invention patent with application number 201010560750.6 discloses an emulsified oil remover for waste drilling fluid and its preparation method, and an epichlorohydrin modified polyether demulsifier is used for harmless treatment of liquid phase after solid-liquid separation of waste drilling fluid. The recovery efficiency is low and it is not suitable for efficient recovery of base oil. The Chinese invention patent with application number 201610346451.X discloses a composite treatment agent for waste vegetable oil-based mud and its preparation method, but for waste oil-based drilling cuttings with high solid content on site, the precipitated liquid phase is still mixed with the solid phase, and a high recovery rate cannot be achieved. The treatment agent has good water solubility, and it is difficult to fully exert its effectiveness for waste mud with high solid content. Therefore, it is necessary to target the high oil content of drilling fluid. The existing commercially available agents have strong hydrophilicity or single demulsification effect, and the direct use of drilling fluid recycling is not ideal, which is not conducive to resource utilization. Summary of the invention
[0006] In view of the defects of the prior art, the present invention provides a method for treating non-aqueous drilling fluid with organic modified iron salt.
[0007] Specifically, the present invention is achieved through the following technical solutions:
[0008] A method for treating non-aqueous drilling fluid with an organic modified iron salt, comprising:
[0009] S1: mixing the organic modified iron salt and the waste non-aqueous drilling fluid to obtain a mixed liquid;
[0010] S2 distills the mixed solution.
[0011] The method for treating non-aqueous drilling fluid with organically modified iron salts mentioned above, wherein the organically modified iron salts include one or more of iron dodecyl sulfonate and iron dodecylbenzene sulfonate.
[0012] In the above-mentioned method for treating non-aqueous drilling fluid with organic modified iron salt, the weight ratio of the waste non-aqueous drilling fluid to the organic modified iron salt is 100:(0.2-1.2).
[0013] In the above method for treating non-aqueous drilling fluid with organic modified iron salt, the mixing and stirring time is 15 to 30 minutes.
[0014] In the above-mentioned method for treating non-aqueous drilling fluid with organic modified iron salt, the distillation pressure is -0.07 to -0.09 MPa, and the distillation time is 30 to 40 minutes.
[0015] The method for treating non-aqueous drilling fluid with organically modified iron salts, wherein the preparation method of the organically modified iron salts comprises:
[0016] S11 separately prepares an anionic surfactant solution and an iron salt solution, and then mixes the two solutions to obtain a mixed solution;
[0017] S12 placing the mixed solution in a water bath for heating to react, forming a precipitate, filtering and washing, and then recrystallizing, filtering, drying, grinding and sieving the formed crystals to obtain an organic modified iron salt; or
[0018] The pH value of the mixed solution is slowly adjusted to 7.0-7.5, and after the adjustment is completed, the mixture is continuously shaken to fully react. After shaking, the precipitate is collected by centrifugation, washed, freeze-dried, ground and sieved to obtain an organic modified iron salt.
[0019] The method for treating non-aqueous drilling fluid with organically modified iron salts, wherein the preparation method of the organically modified iron salts comprises:
[0020] S21: mixing anionic surfactant solid and iron salt to obtain a mixed solid phase;
[0021] S22: placing the mixed solid phase in a ball mill, taking out the mixed solid phase after ball milling, washing and recrystallizing, filtering, drying, grinding and sieving the formed crystals to obtain the organic modified iron salt.
[0022] In the above-mentioned method for treating non-aqueous drilling fluid with organic modified iron salt, the anionic surfactant includes one of sodium dodecyl sulfate and sodium dodecylbenzene sulfonate; the iron salt includes ferric chloride, ferrous chloride, ferric sulfate, ferrous sulfate, ferric nitrate, and ferrous nitrate.
[0023] In the above-mentioned method for treating non-aqueous drilling fluid with organic modified iron salt, in step S11, the anionic surfactant solution is a sodium dodecyl sulfate solution with a concentration of 0.15-0.3 mol / L or a sodium dodecylbenzene sulfonate solution with a concentration of 2.4-3.6 mol / L; the concentration of the iron salt solution is 0.05-0.1 mol / L or 0.8-1.2 mol / L.
[0024] In the above-mentioned method for treating non-aqueous drilling fluid with organic modified iron salt, in step S12, the heating temperature is 50-70°C, and the reaction time is 1-4 hours; the alkali solution drop acceleration rate for slowly adjusting the pH value of the mixed solution is 1-3 mL / min, and the alkali solution for slowly adjusting the pH value of the mixed solution is 5 mol / L NaOH solution; the washing condition is water flushing until the conductivity of the suspension is less than 100 μS / cm.
[0025] In the above-mentioned method for treating non-aqueous drilling fluid with organic modified iron salt, in step S12, the drying is vacuum drying or vacuum freeze drying; the vacuum drying temperature is 40-50°C, and the drying time is 24h; the vacuum freeze drying temperature is 30-50°C, and the drying time is 20-24h.
[0026] In the above-mentioned method for treating non-aqueous drilling fluid with organic modified iron salt, the molar ratio of the anionic surfactant solid to the iron salt is (1-5):1, preferably 3:1.
[0027] In the above-mentioned method for treating non-aqueous drilling fluid with organic modified iron salt, in step S22, the ball milling time is 2h to 5h; the washing condition is water flushing until the conductivity of the suspension is less than 100μS / cm; the drying is vacuum drying, the temperature is 40-50°C, and the drying time is 24h.
[0028] Compared with the prior art, the technical solution of the present invention has the following beneficial effects:
[0029] (1) The method for preparing organic modified iron salt of the present invention adopts simple ion exchange, complexation, copolymerization and mechanical ball milling to prepare anionic surfactant iron salt composite material, which enriches its surface functional groups and enhances its reaction activity while retaining the original morphology of alkyl (benzene) sulfonate;
[0030] (2) Compared with organic surfactants and iron salt compounds, the organic modified iron salt prepared by the present invention can significantly improve the treatment efficiency of waste non-aqueous drilling fluid by synergistic thermal distillation, thereby achieving the purpose of resource utilization and harmless disposal;
[0031] (3) The method of treating non-aqueous drilling fluid with organic modified iron salt of the present invention has a simple technical solution and process, convenient operation, scientific principle, high energy utilization rate, reduced pollution, and environmental friendliness. BRIEF DESCRIPTION OF THE DRAWINGS
[0032] Various other advantages and benefits will become apparent to those of ordinary skill in the art by reading the following detailed description of the preferred embodiment.The drawings are only for the purpose of illustrating the preferred embodiments and are not to be construed as limiting the invention.
[0033] Figure 1 The X-ray diffraction (XRD) pattern of the iron salt bifunctional composite material modified by sodium dodecyl sulfonate and sodium dodecylbenzene sulfonate prepared in Example;
[0034] Figure 2A This is a scanning electron microscope (SEM) image of the sodium dodecyl sulfate-modified iron salt bifunctional composite material prepared in Example;
[0035] Figure 2B This is a scanning electron microscope (SEM) image of the sodium dodecylbenzenesulfonate-modified iron salt bifunctional composite material prepared in Example;
[0036] Figure 3A comparison chart of the liquid phase products of the catalytic synergistic thermal distillation treatment of waste non-aqueous drilling fluid by the sodium dodecyl sulfonate and sodium dodecylbenzene sulfonate modified iron salt bifunctional composite material prepared in the example and the raw material for preparing the organic iron salt agent in the comparative example;
[0037] Figure 4 The effect diagram of the liquid phase recovery rate of the catalytic synergistic thermal distillation treatment of the waste non-aqueous drilling fluid by the sodium dodecyl sulfonate and sodium dodecylbenzene sulfonate-iron salt bifunctional composite material prepared in the example and the raw material for preparing the organic iron salt agent in the comparative example;
[0038] Figure 5 The consumption reduction effect diagram of the catalytic synergistic thermal distillation treatment of waste non-aqueous drilling fluid by the sodium dodecyl sulfonate and sodium dodecylbenzene sulfonate-iron salt bifunctional composite material prepared in the example and the raw material for preparing the organic iron salt agent in the comparative example;
[0039] Figure 6 This is a diagram showing the liquid phase recovery rate of the catalytic synergistic thermal distillation treatment of waste non-aqueous drilling fluid by the sodium dodecyl sulfate and sodium dodecylbenzene sulfonate-iron salt dual-functional composite material prepared in the example and the commercially available medicine in the comparative example.
[0040] Figure 7 This is a diagram showing the consumption reduction effect of the catalytic synergistic thermal distillation treatment of waste non-aqueous drilling fluid using the sodium dodecyl sulfate and sodium dodecylbenzenesulfonate-iron salt bifunctional composite material prepared in the example and the commercially available drugs in the comparative example.
[0041] Figure 8 This is a diagram showing the liquid phase recovery rate of the sodium dodecyl sulfate-iron salt dual-functional composite material prepared in Example 1 in Comparative Example 3.
[0042] Fig. 9 This is a diagram showing the consumption reduction effect of the sodium dodecyl sulfate-iron salt dual-functional composite material prepared in Example 1 in application comparative example 3.
[0043] Fig.10 The GC-MS total ion current diagram of oil recovered from waste non-aqueous drilling fluid catalyzed by synergistic thermal distillation and thermal distillation without additives using the sodium dodecyl sulfate-modified iron salt bifunctional composite material prepared in the comparative example. DETAILED DESCRIPTION
[0044] In order to fully understand the purpose, features and effects of the present invention, the present invention is described in detail through the following specific embodiments. Except for the following contents, the process method of the present invention adopts conventional methods or devices in the art. Unless otherwise specified, the following terms have the meanings commonly understood by those skilled in the art.
[0045] When a numerical range is disclosed herein, the above range is considered to be continuous and includes the minimum and maximum values of the range, as well as every value between such minimum and maximum values. Further, when a range refers to an integer, every integer between the minimum and maximum values of the range is included. In addition, when multiple ranges are provided to describe a feature or characteristic, the ranges can be combined. In other words, unless otherwise indicated, all ranges disclosed herein should be understood to include any and all subranges included therein.
[0046] In this document, the terms "organically modified iron salt", "organically modified iron salt composite material" and "bifunctional organically modified iron salt" have the same meaning and can be used interchangeably.
[0047] In view of the problems of low treatment efficiency and high energy consumption in treating waste non-aqueous drilling fluid with thermal distillation technology, the present invention provides a method for treating waste non-aqueous drilling fluid with bifunctional organic modified iron salt catalysis and synergistic thermal distillation, which not only greatly reduces the energy consumption problem in the process of treating waste non-aqueous drilling fluid, but also improves the treatment efficiency of thermal distillation and the oil phase recovery rate. The high-quality recovered oil after treatment can continue to configure non-aqueous drilling fluid.
[0048] Specifically, the method for treating non-aqueous drilling fluid with organic modified iron salt provided by the present invention comprises: S1: mixing and stirring the organic modified iron salt and the waste non-aqueous drilling fluid uniformly to obtain a mixed liquid; S2: distilling the mixed liquid.
[0049] The technical solution provided by the present invention utilizes a bifunctional organic modified iron salt catalytic synergistic thermal distillation to treat waste non-aqueous drilling fluid. The use of this synergistic agent in combination with thermal distillation is more conducive to changing the microscopic interface properties of the waste non-aqueous drilling fluid to achieve the effect of breaking the stability of multiphase colloids; it is more conducive to catalytic synergistic thermal distillation technology, reducing the reaction activation energy while allowing oil substances to precipitate at a lower temperature, so as to achieve the purpose of separating the base oil in the drilling fluid with low energy consumption. The present invention effectively achieves the purpose of energy saving and consumption reduction through the synergistic distillation of demulsification and catalytic viscosity reduction and its application in the recycling of waste non-aqueous drilling fluid.
[0050] In some preferred embodiments, the organically modified iron salt includes one or more of iron dodecyl sulfonate and iron dodecylbenzene sulfonate.
[0051] In the organic modified iron salt of the present invention, the alkane or alkylbenzene sulfonate of the hydrophobic group has a special surface activity and is a typical asphaltene dispersant. The iron salt can achieve the breaking of the carbon-sulfur bond in the asphaltene through catalysis, resulting in a decrease in the asphaltene content and an increase in the saturation and aromatic content, which ultimately effectively reduces the viscosity of the drilling fluid and improves the distillation efficiency, thereby achieving energy saving and consumption reduction in the distillation process.
[0052] In some preferred embodiments, the weight ratio of the waste non-aqueous drilling fluid to the organic modified iron salt is 100:(0.2-1.2).
[0053] In practice, when the ratio of the organic modified iron salt is too small, the agent cannot be fully mixed with the drilling fluid to play a role; when the ratio of the organic modified iron salt is too large, the processing cost is increased.
[0054] Optionally, the mixing and stirring time is 15 to 30 minutes; the distillation pressure is -0.07 to -0.09 MPa, and the distillation time is 30 to 40 minutes.
[0055] The thermal distillation treatment equipment used in the distillation process includes a high-temperature heating jacket, a double-mouth round-bottom flask, a Kirschner fractionation head, a vacuum capillary, a screw-mouth thermometer sleeve, a thermometer, a serpentine condenser, a vacuum receiving tube, a single-mouth recovery bottle, a vacuum pressure gauge, a safety bottle, a water-type circulating vacuum pump and a smart meter. The connection relationship between each component or each device is carried out according to the existing technology, and the present invention does not specifically limit this.
[0056] Among them, the heating method of thermal distillation includes at least one of electromagnetic heating, microwave heating and fuel combustion heating.
[0057] In some optional embodiments, the organic modified iron salt is prepared by a solution replacement method, and the specific preparation method includes:
[0058] S11: preparing an anionic surfactant solution and an iron salt solution respectively, and then mixing the two solutions to obtain a mixed solution;
[0059] S12: placing the mixed solution in a water bath for heating to react, forming a precipitate, filtering and washing, and then recrystallizing, filtering, drying, grinding and sieving the formed crystals to obtain an organic modified iron salt; or
[0060] The pH value of the mixed solution is slowly adjusted to 7.0-7.5, and after the adjustment is completed, the mixture is continuously shaken to fully react. After shaking, the precipitate is collected by centrifugation, washed, freeze-dried, ground and sieved to obtain an organic modified iron salt.
[0061] Preferably, when the anionic surfactant solution is a sodium dodecylsulfonate solution with a concentration of 0.15 to 0.3 mol / L, the iron salt solution is a 0.05 to 0.1 mol / L ferric chloride solution; when the anionic surfactant solution is a sodium dodecylbenzenesulfonate solution with a concentration of 2.4 to 3.6 mol / L, the iron salt solution is a 0.8 to 1.2 mol / L ferric chloride solution.
[0062] Preferably, the heating temperature is 50-70° C., and the reaction time is 1-4 hours.
[0063] Preferably, the alkali solution for slowly adjusting the pH value of the mixed solution has a drop acceleration rate of 1 to 3 mL / min, and the alkali solution for slowly adjusting the pH value of the mixed solution is a 5 mol / L NaOH solution.
[0064] Preferably, the washing condition is to rinse with water until the conductivity of the suspension is less than 100 μS / cm, thereby fully washing away the unreacted anionic surfactant and iron salt.
[0065] Preferably, the drying is vacuum drying or vacuum freeze drying, wherein the temperature of the vacuum drying is 40-50°C and the drying time is 24 hours; the temperature of the vacuum freeze drying is 30-50°C and the drying time is 20-24 hours.
[0066] In some other optional embodiments, the organic modified iron salt is prepared by mechanical ball milling, and the specific preparation method includes:
[0067] S21: mixing anionic surfactant solid and iron salt to obtain a mixed solid phase;
[0068] S22: placing the mixed solid phase in a ball mill, taking out the mixed solid phase after ball milling, washing and recrystallizing, filtering, drying, grinding and sieving the formed crystals to obtain an organic modified iron salt.
[0069] Preferably, the anionic surfactant includes one or both of sodium dodecyl sulfonate and sodium dodecylbenzene sulfonate; and the iron salt is FeCl3·6H2O.
[0070] Preferably, the molar ratio of the anionic surfactant solid to the iron salt is (1-5):1, thereby obtaining a higher product yield. When the molar ratio of the anionic surfactant solid to the iron salt is 3:1, the yield is as high as 59.46%.
[0071] Preferably, the ball milling time is 2 to 5 hours.
[0072] Preferably, the washing condition is to rinse with water until the conductivity of the suspension is less than 100 μS / cm, thereby fully washing away the unreacted anionic surfactant and iron salt.
[0073] Preferably, the drying is vacuum drying at a temperature of 40-50° C. and a drying time of 24 hours.
[0074] The organic modified iron salt of the present invention has a simple preparation process, is non-hazardous, will not affect the properties of the recovered oil, and avoids secondary pollution.
[0075] The organic modified iron salt prepared by the solution replacement method or the ball milling method of the present invention is an amphiphilic iron dodecyl (benzene) sulfonate. Iron dodecyl (benzene) sulfonate is added to a hot distillation device as an amphiphilic material to synergistically treat water-in-oil drilling fluid, which can effectively play the effects of demulsification, catalysis and viscosity reduction under high temperature. Compared with the distillation treatment of water-in-oil drilling waste fluid without adding an agent or adding / compounding demulsification and catalysis separately, adding a composite agent containing iron dodecyl (benzene) sulfonate has the effect of high liquid phase recovery rate and reducing the system energy consumption of treating waste non-aqueous drilling fluid by distillation.
[0076] Example
[0077] The present invention is further described below by way of examples, but the present invention is not limited to the scope of the examples. The experimental methods in the following examples without specifying specific conditions are carried out according to conventional methods and conditions. The raw materials used in the following examples are all conventionally purchased.
[0078] Example 1: Preparation of sodium dodecyl sulfate modified iron salt composite material by solution replacement method
[0079] The weighed sodium dodecyl sulfate was added into ultrapure water and mixed evenly to obtain a sodium dodecyl sulfate solution with a concentration of 0.15 mol / L; a 0.05 mol / L ferric chloride solution was prepared in the same manner; sodium dodecyl sulfate and ferric chloride were heated and mixed at a molar ratio of 3:1 at 70°C for 2 h by a solution replacement method to obtain ferric dodecyl sulfate crystals, which were vacuum filtered and washed with water before recrystallization. After the filtrate was free of foam and the conductivity was less than 100 μS / cm, the filter residue was dried in an oven at 50°C for 24 h, and the obtained yellow powder was sealed and stored to obtain a sodium dodecyl sulfate modified iron salt composite material.
[0080] Example 2: Preparation of sodium dodecyl sulfate modified iron salt composite material by solution replacement method
[0081] The weighed sodium dodecyl sulfate was added into ultrapure water and mixed evenly to obtain a sodium dodecyl sulfate solution with a concentration of 0.3 mol / L. Similarly, a 0.15 mol / L ferric chloride solution was prepared. The mixture was heated and mixed at 70°C for 2 h in a molar ratio of 3:1 by a solution replacement method to obtain iron dodecyl sulfate crystals. The crystals were vacuum filtered and washed with water for recrystallization. After the filtrate was free of foam and the conductivity was less than 100 μS / cm, the filter residue was dried in an oven at 50°C for 24 h. The obtained yellow powder was sealed and stored to obtain a sodium dodecyl sulfate modified iron salt composite material.
[0082] Example 3: Preparation of iron salt composite material modified by sodium dodecylbenzenesulfonate by solution replacement method
[0083] Sodium dodecylbenzene sulfonate was added to ultrapure water and mixed evenly. A 2.4 mol / L sodium dodecylbenzene sulfonate solution was mixed with a 0.8 mol / L ferric chloride solution by solution replacement method, and stirred thoroughly to obtain a mixed solution. Subsequently, a 5 mol / L NaOH solution was slowly added to the mixed solution with a dropper at a rate of 2 mL / min, and the pH value was adjusted to 7.0 by continuous dropwise addition. After adjustment, the obtained system was transferred to a polyethylene bottle, and the bottle was sealed and continued to oscillate for 2 hours. After the oscillation was completed, the mixture was centrifuged and the obtained precipitate was rinsed with ultrapure water until the conductivity of the suspension was less than 100 μS / cm. Excess water was then removed in a -40°C vacuum freeze dryer. The obtained dark red powder was ground and sealed to obtain an iron salt composite material modified with sodium dodecylbenzene sulfonate.
[0084] Example 4: Preparation of iron salt composite material modified by sodium dodecylbenzenesulfonate by solution replacement method
[0085] Sodium dodecylbenzene sulfonate was added to ultrapure water and mixed evenly to obtain a sodium dodecylbenzene sulfonate solution with a concentration of 3.6 mol / L and a ferric chloride solution with a concentration of 1.2 mol / L. The two were mixed and stirred thoroughly according to the solution replacement method to obtain a mixed solution. Subsequently, a 5 mol / L NaOH solution was slowly added to the mixed solution with a dropper at a rate of 2 mL / min, and the pH value was adjusted to 7.0 by continuous dropwise addition. After the adjustment, the obtained system was transferred to a polyethylene bottle, and the bottle was sealed and continued to oscillate for 2 hours. After the oscillation was completed, the solution was centrifuged and the obtained precipitate was rinsed with ultrapure water until the conductivity of the suspension was less than 100 μS / cm. Excess water was then removed in a -40°C vacuum freeze dryer. The obtained dark red powder was ground and sealed to obtain an iron salt composite material modified with sodium dodecylbenzene sulfonate.
[0086] Example 5: Preparation of sodium dodecyl sulfate modified iron salt composite material by mechanical ball milling
[0087] 0.15 mol of sodium dodecyl sulfate and 0.05 mol of iron salt were mechanically mixed in a ball mill for 2 hours by mechanical ball milling. The mixture was taken out and filtered with pure water for washing and recrystallization. The conductivity of the filtrate was washed with water until it was less than 100 μS / cm. The crystals were placed on the filter residue and dried in an oven at 50°C for 24 hours. The obtained product was ground into powder and sealed for storage to obtain a sodium dodecyl sulfate modified iron salt composite material.
[0088] Example 6: Preparation of sodium dodecyl sulfate modified iron salt composite material by mechanical ball milling
[0089] 0.3 mol of sodium dodecyl sulfate and 0.1 mol of trivalent iron salt were mechanically mixed in a ball mill for 5 hours by mechanical ball milling. The mixture was taken out and filtered with pure water for washing and recrystallization. The conductivity of the filtrate was washed with water until it was less than 100 μS / cm. The crystals were placed on the filter residue and dried in an oven at 50°C for 24 hours. The obtained product was ground into powder and sealed for storage to obtain a sodium dodecyl sulfate modified iron salt composite material.
[0090] Example 7: Preparation of sodium dodecylbenzenesulfonate modified iron salt composite material by mechanical ball milling
[0091] 2.4 mol of sodium dodecylbenzene sulfonate and 0.8 mol of iron salt were mechanically mixed in a ball mill for 2 hours by mechanical ball milling. The mixture was taken out and filtered with pure water for washing and recrystallization. The conductivity of the filtrate was washed with water until it was less than 100 μS / cm. The crystals were placed on the filter residue and dried in an oven at 50°C for 24 hours. The obtained product was ground into powder and sealed for storage to obtain a sodium dodecylbenzene sulfonate modified iron salt composite material.
[0092] Example 8: Preparation of sodium dodecylbenzenesulfonate modified iron salt composite material by mechanical ball milling
[0093] 3.6 mol of sodium dodecylbenzene sulfonate and 1.2 mol of iron salt were mechanically mixed in a ball mill for 5 hours by mechanical ball milling. The mixture was taken out and filtered with pure water for washing and recrystallization until the conductivity of the filtrate was less than 100 μS / cm. The crystals were then placed on the filter residue and dried in an oven at 50°C for 24 hours. The obtained product was ground into powder and sealed for storage to obtain a sodium dodecylbenzene sulfonate modified iron salt composite material.
[0094] Test example: Performance characterization of modified iron salt composite materials
[0095] The relevant characteristics of the iron salt composite material modified by sodium dodecyl sulfonate and sodium dodecylbenzene sulfonate prepared in Examples 1 and 3 are as follows: Figure 1 , Figure 2A and Figure 2B shown. Figure 1 The X-ray diffraction (XRD) diagram of two iron salt composite materials modified by two different organic solutions, sodium dodecyl sulfonate and sodium dodecylbenzene sulfonate, is compared. The characteristic peaks in the diagram indicate that the prepared iron salt composite materials modified by sodium dodecyl sulfonate and sodium dodecylbenzene sulfonate are both dilinear iron salt composite materials. Figure 2A and Figure 2B This is a scanning electron microscope (SEM) image comparing the iron salt composite material modified by two different organic solutions, sodium dodecyl sulfonate and sodium dodecylbenzene sulfonate. There is no obvious morphological difference between the iron salt composite material modified by two different organic solutions, sodium dodecyl sulfonate and sodium dodecylbenzene sulfonate.
[0096] After testing, the sodium dodecylsulfonate modified iron salt composite materials or sodium dodecylbenzenesulfonate modified iron salt composite materials prepared in Example 2 and Examples 4-8 have the same characteristics and morphology as the composite materials prepared in Example 1 or 3. The properties of the composite materials can be referred to Figure 1 , Figure 2A and Figure 2B .
[0097] Application Example 1
[0098] 1 wt % of the sodium dodecyl sulfate modified iron salt bifunctional composite material synthesized in Example 1 was added, mixed with 100 g of waste non-aqueous drilling fluid and stirred for 15 minutes, and then placed in a -0.07 MPa hot distillation device for catalytic synergistic treatment. The experiment was terminated when the thermometer temperature dropped to 50°C after rising. The distillation temperature, distillation time and smart meter power consumption were recorded, and the liquid phase recovery rate and the residual solid oil content were analyzed.
[0099] Application Example 2
[0100] 1 wt % of the sodium dodecyl sulfate modified iron salt bifunctional composite material synthesized in Example 2 was added, mixed with 100 g of waste non-aqueous drilling fluid and stirred for 15 minutes, and then placed in a hot distillation device at -0.07 MPa for catalytic synergistic treatment. The experiment was terminated when the thermometer temperature dropped to 50°C after rising. The distillation temperature, distillation time and smart meter power consumption were recorded, and the liquid phase recovery rate and the residual solid oil content were analyzed.
[0101] Application Example 3
[0102] 1 wt % of the sodium dodecylbenzenesulfonate modified iron salt bifunctional composite material synthesized in Example 3 was added, mixed with 100 g of waste non-aqueous drilling fluid and stirred for 15 minutes, and then placed in a hot distillation device at -0.07 MPa for catalytic synergistic treatment. The experiment was terminated when the thermometer temperature dropped to 50°C after rising. The distillation temperature, distillation time and smart meter power consumption were recorded, and the liquid phase recovery rate and the residual solid oil content were analyzed.
[0103] Application Example 4
[0104] 1 wt % of the sodium dodecylbenzenesulfonate modified iron salt bifunctional composite material synthesized in Example 4 was added, mixed with 100 g of waste non-aqueous drilling fluid and stirred for 15 minutes, and then placed in a hot distillation device at -0.07 MPa for catalytic synergistic treatment. The experiment was terminated when the thermometer temperature dropped to 50°C after rising. The distillation temperature, distillation time and smart meter power consumption were recorded, and the liquid phase recovery rate and the residual solid oil content were analyzed.
[0105] The liquid products of application examples 1-4 are as follows Figure 3The results of liquid phase recovery and residual solid oil content are shown in Figure 4 As shown in the figure, the distillation temperature, distillation time and power consumption of the smart meter are as follows Figure 5 As shown. Among them, Figure 3 In each picture, the small bottle on the left contains an oil-water mixture, and the large bottle on the right contains recovered oil.
[0106] The results show that after adding sodium dodecyl sulfonate modified iron salt bifunctional composite material and sodium dodecylbenzene sulfonate modified iron salt bifunctional composite material, the liquid phase recovery rate is increased by 6-7%, and the system power consumption is reduced by 15%; the sodium dodecyl sulfonate modified iron salt bifunctional composite material is better than the sodium dodecylbenzene sulfonate modified iron salt bifunctional composite material, which is related to the presence of benzene rings on sodium dodecylbenzene sulfonate and the steric hindrance effect. The two agents prepared at different concentrations have the same effect. The sodium dodecyl sulfonate and sodium dodecylbenzene sulfonate modified iron salt bifunctional composite materials prepared in Example 1-2 do not apparently affect the basic properties of the oil recovered by thermal distillation.
[0107] Application Example 5
[0108] 0.2-1.2 wt% of sodium dodecyl sulfate modified iron salt bifunctional composite material (C 12 H 25 SO3)3Fe), mixed with 100g of waste non-aqueous drilling fluid and stirred for 15min, was placed in a -0.07MPa hot distillation device for catalytic synergistic treatment. The experiment was terminated when the thermometer temperature dropped to 50℃ after rising. The distillation temperature, distillation time and power consumption of the smart meter were recorded, and the liquid phase recovery rate and residual solid oil content were analyzed.
[0109] Application Example 5 Results Figure 8 and Fig. 9 As shown. 12 H 25 The liquid phase recovery rate increased with the increase of the amount of Fe added, from 86.90% without reagent to 1wt% (C 12 H 25 SO3)3Fe 93.73%. Add 1wt% (C 12 H 25 SO3)3Fe, the temperature of oil-based drilling fluid treated by the decompression system is reduced by 40℃, the distillation time is reduced to 27min, and the consumption is reduced by 15.54%. When the addition amount is increased to 1.2wt%, the changes in various indicators are not large.
[0110] Application Example 6
[0111] The bifunctional composite material modified with sodium dodecyl sulfate synthesized by adding 1wt% 5 was mixed with 100g of waste non-aqueous drilling fluid and stirred for 15min, and then placed in a hot distillation device at -0.07MPa for catalytic synergistic treatment. The experiment was terminated when the temperature of the thermometer dropped to 50℃ after rising. The distillation temperature, distillation time and power consumption of the smart meter were recorded, and the liquid phase recovery rate and the residual solid oil content were analyzed.
[0112] Application Example 7
[0113] The bifunctional composite material modified with sodium dodecyl sulfate synthesized by adding 1wt% 6 was mixed with 100g of waste non-aqueous drilling fluid and stirred for 15min, and then placed in a hot distillation device at -0.07MPa for catalytic synergistic treatment. The experiment was terminated when the thermometer temperature dropped to 50℃ after rising. The distillation temperature, distillation time and power consumption of the smart meter were recorded, and the liquid phase recovery rate and the residual solid oil content were analyzed.
[0114] The liquid phase recovery rate and power consumption of the dual-functional composite material modified with sodium dodecyl sulfate in application example 6-7 are basically consistent with the results in example 1-2.
[0115] Application Example 8
[0116] 1 wt % of the sodium dodecylbenzenesulfonate modified iron salt bifunctional composite material synthesized in Example 7 was added, mixed with 100 g of waste non-aqueous drilling fluid and stirred for 15 minutes, and then placed in a hot distillation device at -0.07 MPa for catalytic synergistic treatment. The experiment was terminated when the thermometer temperature dropped to 50°C after rising. The distillation temperature, distillation time and power consumption of the smart meter were recorded, and the liquid phase recovery rate and the residual solid oil content were analyzed.
[0117] Application Example 9
[0118] 1 wt % of the sodium dodecylbenzenesulfonate modified iron salt bifunctional composite material synthesized in Example 8 was added, mixed with 100 g of waste non-aqueous drilling fluid and stirred for 15 minutes, and then placed in a hot distillation device at -0.07 MPa for catalytic synergistic treatment. The experiment was terminated when the thermometer temperature dropped to 50°C after rising. The distillation temperature, distillation time and smart meter power consumption were recorded, and the liquid phase recovery rate and the residual solid oil content were analyzed.
[0119] The liquid phase recovery rate and power consumption of the dual-functional composite material modified with sodium dodecylbenzenesulfonate and iron salt in application examples 8-9 are basically consistent with the results in examples 3-4.
[0120] Application Example 10
[0121] 1 wt % of the sodium dodecyl sulfate modified iron salt bifunctional composite material synthesized in Example 1 was added, mixed with 100 g of waste non-aqueous drilling fluid and stirred for 15 minutes, and then placed in a hot distillation device at -0.09 MPa for catalytic synergistic treatment. The experiment was terminated when the thermometer temperature dropped to 50°C after rising. The distillation temperature, distillation time and smart meter power consumption were recorded, and the liquid phase recovery rate and the residual solid oil content were analyzed.
[0122] Application Example 11
[0123] 1 wt % of the sodium dodecyl sulfate modified iron salt bifunctional composite material synthesized in Example 5 was added, mixed with 100 g of waste non-aqueous drilling fluid and stirred for 15 minutes, and then placed in a hot distillation device at -0.09 MPa for catalytic synergistic treatment. The experiment was terminated when the thermometer temperature dropped to 50°C after rising. The distillation temperature, distillation time and smart meter power consumption were recorded, and the liquid phase recovery rate and the residual solid oil content were analyzed.
[0124] In application example 10-11, the liquid phase recovery rate and power consumption of the synergistic dual-functional composite material modified with sodium dodecyl sulfate at -0.09 MPa are basically consistent with the results at -0.07 MPa.
[0125] Application Example 12
[0126] 1 wt % of the sodium dodecyl sulfate modified iron salt bifunctional composite material synthesized in Example 1 was added, mixed with 100 g of waste non-aqueous drilling fluid and stirred for 30 minutes, and then placed in a hot distillation device at -0.07 MPa for catalytic synergistic treatment. The experiment was terminated when the thermometer temperature dropped to 50°C after rising. The distillation temperature, distillation time and smart meter power consumption were recorded, and the liquid phase recovery rate and the residual solid oil content were analyzed.
[0127] Application Example 13
[0128] 1 wt % of the sodium dodecyl sulfate modified iron salt bifunctional composite material synthesized in Example 5 was added, mixed with 100 g of waste non-aqueous drilling fluid and stirred for 30 minutes, and then placed in a hot distillation device at -0.07 MPa for catalytic synergistic treatment. The experiment was terminated when the thermometer temperature dropped to 50°C after rising. The distillation temperature, distillation time and smart meter power consumption were recorded, and the liquid phase recovery rate and the residual solid oil content were analyzed.
[0129] In application example 12-13, the liquid phase recovery rate and power consumption of the dual-functional composite material of sodium dodecyl sulfate modified iron salt mixed with the drilling fluid for 30 minutes were basically consistent with the results of mixing and stirring for 15 minutes.
[0130] Comparative application example 1:
[0131] Sodium dodecyl sulfonate, sodium dodecylbenzene sulfonate, and FeCl3·6H2O, all with a concentration of 1wt%, were mixed with 100g of waste non-aqueous drilling fluid and stirred for 15 minutes, then placed in a -0.07MPa hot distillation device to compare the synergistic treatment of distillation and reagents. The experiment was terminated when the temperature of the thermometer dropped to 50°C after rising, and the temperature, time, and power consumption of the smart meter of the hot distillation synergistic reagent treatment were recorded, and the liquid recovery rate and residual solid oil content were analyzed.
[0132] Comparative application example 2:
[0133] Commercially available propylene glycol block polyether (BASF-L64), water-soluble catalyst (KOH), oil-soluble catalyst (C 15 H 24 FeO6) was mixed with 100g of waste non-aqueous drilling fluid and stirred for 15 minutes, then placed in a -0.07MPa hot distillation device for a comparison of distillation and reagent synergistic treatment. The experiment was terminated when the temperature of the thermometer dropped to 50°C after rising, and the distillation temperature, distillation time and smart meter power consumption of the hot distillation synergistic treatment were recorded, and the liquid phase recovery rate and residual solid oil content were analyzed.
[0134] Comparing the results of application examples 1 and 2, Figures 4 to 7 As shown, (C 12 H 25 SO3)3Fe has a better effect on synergistic distillation than other synergistic agents, with a liquid phase recovery rate of 93% and a synergistic consumption reduction of 15.54%. It mainly contacts asphaltene through the hydrogen bond of O=S=O and OH or CH and is absorbed to the surface to further promote the pyrolysis of heavy oil components; while Fe 3+ The heteroatom compounds further form strong interactions with heavy oil molecules (asphaltene and heteroatom compounds) and N and S, which reduces the bond energy of CC, CN and CS on the heteroatom molecules, thereby reducing the activation energy of the bonds and breaking them, ultimately leading to the cracking of heavy oil components.
[0135] Figure 4 to Figure 7 The results show that compared with commercially available catalysts, the liquid phase recovery rate of the iron salt composite material modified by sodium dodecyl sulfonate and sodium dodecylbenzene sulfonate prepared in the example is further improved, and the remaining solid oil content can meet the emission standards. The results show that under the same addition amount, the composite material prepared in the example synergizes with thermal distillation to reduce energy consumption by up to 15.54%, and the consumption reduction effect is significantly improved.
[0136] The GC-MS total ion current of the waste non-aqueous drilling fluid recovered oil catalyzed by the sodium dodecyl sulfate modified iron salt composite material prepared in Example 1 and the thermal distillation without additives was compared (the comparison results are shown in Fig.10 )). From a microscopic perspective, the main components of the recovered oil from the waste non-aqueous drilling fluid treated by thermal distillation before and after the addition of the agent remain basically unchanged, and the peak time is roughly the same, which is feasible for the re-mixing of drilling fluid.
[0137] The present invention has been disclosed above with preferred embodiments, but those skilled in the art should understand that these embodiments are only used to describe the present invention and should not be understood as limiting the scope of the present invention. It should be noted that all changes and substitutions equivalent to these embodiments should be deemed to be included in the scope of the claims of the present invention. Therefore, the scope of protection of the present invention should be based on the scope defined in the claims.
Claims
1. A method for treating non-aqueous drilling fluid with organic modified iron salt, characterized in that: include: S1: mixing the organic modified iron salt and the waste non-aqueous drilling fluid to obtain a mixed liquid; S2 distills the mixed solution.
2. The method according to claim 1, characterized in that The organic modified iron salt includes one or more of iron dodecyl sulfonate and iron dodecylbenzene sulfonate.
3. The method according to claim 1, characterized in that The weight ratio of the waste non-aqueous drilling fluid to the organic modified iron salt is 100:(0.2-1.2).
4. The method according to claim 1, characterized in that: The mixing and stirring time is 15 to 30 minutes.
5. The method according to claim 1, characterized in that The distillation pressure is -0.07 to -0.09 MPa, and the distillation time is 30 to 40 minutes.
6. The method according to claim 1, characterized in that The preparation method of the organic modified iron salt comprises: S11 separately prepares an anionic surfactant solution and an iron salt solution, and then mixes the two solutions to obtain a mixed solution; S12 placing the mixed solution in a water bath for heating to react, forming a precipitate, filtering and washing, and then recrystallizing, filtering, drying, grinding and sieving the formed crystals to obtain an organic modified iron salt; or The pH value of the mixed solution is slowly adjusted to 7.0-7.5, and after the adjustment is completed, the mixture is continuously shaken to fully react. After shaking, the precipitate is collected by centrifugation, washed, freeze-dried, ground and sieved to obtain an organic modified iron salt.
7. The method according to claim 1, characterized in that The preparation method of the organic modified iron salt comprises: S21: mixing anionic surfactant solid and iron salt to obtain a mixed solid phase; S22: placing the mixed solid phase in a ball mill, taking out the mixed solid phase after ball milling, washing and recrystallizing, filtering, drying, grinding and sieving the formed crystals to obtain the organic modified iron salt.
8. The method according to claim 6 or 7, characterized in that: The anionic surfactant includes one of sodium dodecyl sulfonate and sodium dodecylbenzene sulfonate; the iron salt includes ferric chloride, ferrous chloride, ferric sulfate, ferrous sulfate, ferric nitrate and ferrous nitrate.
9. The method according to claim 6, characterized in that In step S11, the anionic surfactant solution is a sodium dodecylsulfonate solution with a concentration of 0.15-0.3 mol / L or a sodium dodecylbenzenesulfonate solution with a concentration of 2.4-3.6 mol / L; the concentration of the iron salt solution is 0.05-0.1 mol / L or 0.8-1.2 mol / L.
10. The method according to claim 6, characterized in that In step S12, the heating temperature is 50-70°C, and the reaction time is 1-4 hours; the alkali solution drop acceleration rate for slowly adjusting the pH value of the mixed solution is 1-3 mL / min, and the alkali solution for slowly adjusting the pH value of the mixed solution is 5 mol / L NaOH solution; the washing condition is water washing until the conductivity of the suspension is less than 100 μS / cm.
11. The method according to claim 6, characterized in that In step S12, the drying is vacuum drying or vacuum freeze drying; the temperature of the vacuum drying is 40-50°C, and the drying time is 24 hours; the temperature of the vacuum freeze drying is 30-50°C, and the drying time is 20-24 hours.
12. The method according to claim 7, characterized in that The molar ratio of the anionic surfactant solid to the iron salt is (1-5):
1.
13. The method according to claim 7, characterized in that In step S22, the ball milling time is 2h to 5h; the washing condition is water washing until the conductivity of the suspension is less than 100μS / cm; the drying is vacuum drying at a temperature of 40 to 50°C and a drying time of 24h.
Citation Information
Patent Citations
Emulsified oil removing agent for waste drilling fluid and preparation method thereof
CN102153181A
A composite treatment agent for waste vegetable oil oil-based mud and its preparation method
CN105800908B